KEPASTIAN HUKUM PELAKSANAAN LELANG TANAH DAN BANGUNAN PADA KREDIT MACET DARI BANK - Hutagalung, Chyntia; Radhitya A. Sadiqien; Diana RW Napitupulu (Honeste Vivere, 2025)
The presence of credit facilities in the community can be used as a solution to meet consumptive needs, both personal and for business people. However, in the midst of the ease of credit facilities provided by the Bank, its implementation is inseparable from challenges and obstacles, namely the occurrence of bad credit. Therefore, when the debtor applying for credit, providing collateral to the bank is one of the ways to guarantee or provide certainty that the proposed debt obligations will be paid back. The form of collateral provided can be in the form of a mortgage on the customer's ownership certificate if it is an immovable asset such as land and buildings. This research uses normative legal research methods, with secondary data, namely ready-made materials or library legal materials. The legal materials used consist of primary, secondary, and non-legal materials. The results showed that in the event of bad credit, the object of mortgage rights used as collateral can be executed through an auction as stipulated in Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land, so that legal certainty in the implementation of land and building auctions on bad credit from banks in principle can provide legal protection for both creditors and debtors.